Optimale Vertragsdifferenzierung in der Agrarumweltpolitik - Thilo Glebe (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2006)
– This article deals with the optimal differentiation of agri-environmental contracts based on a self-selection mechanism. The paper demonstrates that both economic efficiency and effectiveness of public expenditures can be increased, if a menu of combinations of farming practices and payments are offered. However, there is a trade-off between efficiency and effectiveness, since the optimal programme minimising government expenses does not simultaneously minimise farmers' opportunity costs. A numerical example of differentiated agri-environmental contracts, aiming for the reduction of nitrogen fertiliser in wheat production, illustrates that efficiency and effectiveness gains can be substantial. Furthermore, it is shown that economic rents for agricultural producers do not necessarily shrink as a result of contract differentiation, if the latter aims for the minimisation of public expenditures.
Keywords: 330; Agrarpolitik; Umweltpolitik; Wirkungsanalyse; Vertragstheorie; Adverse Selektion